Socioeconomic characteristics of the population living in Roma settlements and their association with health and health-related behaviour - Gecková, Andrea Madarasová; Babinská, Ingrid; Bobáková, Daniela; Veselská, Zuzana Dankulincová; Bosáková, Lucia; Kolarcik, Peter; Jarcuska, Peter; Pella, Daniel; Halánová, Monika; HepaMeta Team (Central European journal of public health, 2014)
BACKGROUND: The aim of this study was to compare socioeconomic characteristics of the Roma population living in Roma settlements with the majority population. Moreover, it was aimed to assess socioeconomic differences in health and health-related behaviour within the population living in Roma settlements. METHODS: Data from the cross-sectional HepaMeta study conducted in Slovakia in 2011 were used. The sample consisted of 452 Roma (mean age = 34.7; 35.2% men) and 403 non-Roma (mean age = 33.5; 45.9% men) respondents. Roma in selected settlements were recruited by local Roma community workers. Respondents from the major population were randomly selected from a list of patients from general practitioners. Data were collected via questionnaire, anthropometric measures and analysed blood samples. Differences in socioeconomic characteristics between the population living in Roma settlements and the majority population were tested using the chi-square test. The contribution of selected socioeconomic characteristics on health and health-related behaviour of the population living in Roma settlements was assessed by logistic regression models adjusted for age and gender. RESULTS: The population living in Roma settlements is characterised by significantly lower socioeconomic standards, and the living conditions are significantly worse compared with the majority. With few exceptions, the study did not confirm any significant association between socioeconomic indicators and health and health-related behaviour within the population living in Roma settlements. CONCLUSIONS: The deteriorating effect of living in Roma settlement on health and health-related behaviour seems to be immense regardless differences in socioeconomic characteristics or living condition within the settlement population.
Keywords: Odds Ratio; Health Status; Romové; Health Surveys; lidé; mladiství; zdravé chování; Adult; Middle Aged; charakteristiky bydlení; Residence Characteristics; rozložení podle pohlaví; Age Distribution; odds ratio; Slovakia; Female; Sex Distribution; průzkumy a dotazníky; zdravotní stav; Adolescent; Humans; Rural Population; průřezové studie; Socioeconomic Factors; Slovenská republika; Cross-Sectional Studies; lidé středního věku; venkovské obyvatelstvo; věkové rozložení; mužské pohlaví; mladý dospělý; společenská třída; Health Behavior; Roma; socioekonomické faktory; ženské pohlaví; Young Adult; zdravotnické přehledy; Male; Social Class; dospělí; Surveys and Questionnaires